Subjective well-being of bumble application users: Viewed from self-esteem and self-disclosure - Agnes Monika; Lucy Hariadi; Riwi Widyastuti (Jurnal Psikologi Tabularasa, 2025)
This study aims to examine the relationship between self-esteem and self-disclosure with subjective well-being among users of the Bumble online dating application in Semarang. The background of this research is based on the increasing use of dating applications as a medium of social interaction, which may influence users’ psychological well-being. Subjective well-being in this study was measured through two key aspects: life satisfaction and affect. This research employed a quantitative approach with a correlational design. The sample consisted of 384 respondents selected using purposive sampling based on specific criteria: aged 18–28 years, having verified accounts, and active use of the Bumble application for more than two years. Data were collected through online questionnaires using the Satisfaction with Life Scale (SWLS), the Positive and Negative Affect Schedule (PANAS), Coopersmith’s self-esteem scale, and Altman & Taylor’s self-disclosure scale. Data analysis was conducted using multiple linear regression with the help of SPSS. The findings indicate that self-esteem and self-disclosure simultaneously have a significant effect on subjective well-being, particularly on life satisfaction (R² = 0.785; p < 0.05). Partially, both variables also showed a significant positive effect on life satisfaction; however, neither had a significant effect on affect, whether simultaneously or individually. The categorization results showed that most respondents had high levels of self-esteem, self-disclosure, and life satisfaction, while affect tended to fall into the moderate category. It can be concluded that self-confidence and openness play an important role in enhancing the subjective well-being of online dating application users, particularly in the cognitive dimension related to life satisfaction evaluation. These findings are expected to contribute to the development of psychological strategies that support the well-being of digital application users such as Bumble, and to offer practical input for application developers in creating features that support users’ subjective well-being, especially in the evaluative aspect of life.